The absence of changes in the relative age effect present an opportunity for lower income soccer clubs to be more efficient than Europe`s elite - Craig, T. P.; Enright, K.; Maughan, P.; Abbott, W.; Navarro, J. F. (PLOS ONE, 2025)
An overrepresentation of athletes born earlier in the year compared with those born later in the year is known as the relative age effect (RAE). This is perceived to be due to physical selection bias which leads to higher degrees of exposure to coaching, physical training and competition at a younger age. Even with increasing knowledge and established interventions, clubs in Europe`s top leagues still present a strong RAE. Scottish clubs have limited resources in comparison meaning academy efficiency is paramount. The main study aim was to assess changes in the RAE over a ten-year period in Scottish soccer. A secondary aim was to establish if physical differences exist across each quarter due to findings in English academy players that maturation status and not RAE is the main discrepancy for physicality. A retrospective analysis of 512 players from a Scottish academy over a ten year period was granted ethical approval. The impact of relative age effect was assessed against anthropometric and physical characteristics. The range of players in each quarter was Q1 37.0-42.9% versus Q2 22.8-32.4%, Q3 11.9-26.0% and Q4 7.1-14.3% with no impact of time on RAE profiles. Odds Ratio analysis indicate a greater chance of selection within the academy when assessing Q1vsQ4 players quarter comparisons (ranging 3.2-5.2 times more likely to be signed). When controlling for age group, multilevel modelling showed there were no significant differences across quarters in physical measures with the exception of a trivial CMJ difference. The lack of progression in the RAE profiles is disappointing however presents an opportunity for increased efficiency. By viewing the RAE as an under representation of Q4 players and using established corrective procedures, this can contribute to the unnecessary release of players from academies due to RAE, thus addressing challenges in financially restricted environments that resource rich environments such as Europe`s elite have not yet overcome.